The Euphemism in “Sambah Manyambah” Tradition of Minangnese Wedding Ceremony - Muhammad . Fauzi; Rahmad . Husein; Sumarsih . . (LINGUISTIK TERAPAN, 2021)
The paper describes the perspective of “Sambah Manyambah” Tradition”(literally ‘to greet a bride-groom up’) tradition and the attempts to analyze the euphemism such tradition which is mainly found in Minangnese regency and becomes an oral tradition that requires indigenous actors who have indigenous knowledge and expertise in speaking and in using indigenous language. The actors are considered customary actors (or pelakuadat) who, in this case, deliver custom speech or tribute (pasambahan or pidatoadat) which is aimed at declaring the intention and the purposes of the tradition. The research method is qualitative descriptive and attempted to obtain the necessary information from informants with observation techniques. The results show that since the actors’ existence is lack of appreciation today, the tradition undergoes significant changes; therefore, a model of this research will take the euphemism to the tradition has been created and is hopefully accepted by local communities. In here the researcher will get the types of euphemism used in ‘Sambah Manyambah’ Tradition for the tradition of Minangnese wedding ceremony. It is suggested that Pariaman should be getting the point of ‘Sambah Manyambah’ Tradition itself.Keywords: Euphemism, Sambah Manyambah, Wedding Ceremony